A self-supporting high-entropy phosphide negative electrode material and a preparation method thereof

CN122907601APending Publication Date: 2026-10-13SHUANGDENG GRP CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611135702.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-29
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

然而,该类材料普遍面临两大关键问题:一是电子导电性较差;二是在钠离子反复嵌入与脱出过程中,易发生体积膨胀甚至结构粉化,导致其在实际应用中的倍率性能和循环寿命难以满足需求

Benefits of technology

[0016]本申请的有益效果是:泡沫铜基底与高熵氢氧化物前驱体通过化学键合实现稳固结合,具体结合机制为:泡沫铜经稀盐酸预处理后,表面氧化层被彻底去除,同时基底表面形成微观粗糙结构与羟基(-OH)活性位点。溶剂热反应过程中,原位生长的高熵氢氧化物中的金属-氧键,可与泡沫铜表面的铜原子通过氧原子形成M-O-Cu(五种金属-氧-铜)桥接化学键,该强界面结合作用在后续高温磷化处理后仍可部分保留,有效保障了高熵磷化物活性物质与泡沫铜基底的结合牢固度,避免循环过程中活性物质脱落,显著提升电极长期循环稳定性,同时泡沫铜本身为高导电三维金属骨架,磷化后基底生成导电Cu3P物相,与五元高熵磷化物晶格匹配度高、界面导电协同作用优异,因此组装电池时无需额外引入粘结剂与导电剂,既避免了粘结剂带来的能量密度损失、离子与电子传输受阻和循环过程活性物质脱落问题,又简化了电极制备工艺。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122907601A_ABST
    Figure CN122907601A_ABST
Patent Text Reader

Abstract

The application discloses a self-supporting high-entropy phosphide negative material and a preparation method thereof, and relates to the technical field of sodium ion batteries. The method comprises the following steps: pretreating foamed copper; preparing a mixed solution by co-dissolving five metal nitrate salts, i.e., cobalt nitrate, nickel nitrate, iron nitrate, copper nitrate and bismuth nitrate, and urea in a solvent; immersing the pretreated foamed copper into the mixed solution to perform a solvothermal reaction; cleaning and drying a hydrothermal product to obtain a foamed copper-loaded high-entropy hydroxide precursor; and performing phosphorization treatment on the foamed copper-loaded high-entropy hydroxide precursor in an inert atmosphere to obtain the self-supporting high-entropy phosphide negative material. The method solves the problems of poor self-conductivity of a negative electrode, serious volume expansion and pulverization during charging and discharging, reduction of battery energy density due to addition of a binder in a traditional electrode preparation process, easy falling off of active substances, and difficulty in simultaneously achieving high capacity, excellent rate and long cycle stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of sodium-ion battery technology, and in particular to a self-supporting high-entropy phosphide anode material and its preparation method. Background Technology

[0002] With the continued rise in global demand for renewable energy and sustainable energy storage solutions, sodium-ion batteries are considered an ideal choice for large-scale energy storage systems due to their abundant resources, significant cost advantages, and similar working mechanism to lithium-ion batteries. However, the large ionic radius and poor reaction kinetics of sodium ions significantly limit the improvement of their energy density, becoming a major bottleneck restricting their practical application.

[0003] Among numerous anode materials, transition metal phosphides have become a research hotspot for sodium-ion batteries due to their high specific capacity and low discharge plateau. However, these materials generally face two key problems: firstly, poor electronic conductivity; and secondly, the repeated insertion and extraction of sodium ions easily leads to volume expansion and even structural pulverization, making it difficult to meet the rate performance and cycle life requirements in practical applications. In traditional electrode fabrication processes, binders and conductive agents need to be added to the slurry before coating it onto the current collector surface. This process has inherent drawbacks: the addition of binders reduces the battery's energy density, and the repeated insertion and extraction of sodium ions during charging and discharging weakens the adhesion between the active material and the current collector, ultimately leading to the detachment of the active material.

[0004] Therefore, existing transition metal phosphides suffer from poor conductivity of the negative electrode itself, severe volume expansion and pulverization during charge and discharge, and the addition of binders in traditional electrode preparation processes can reduce battery energy density and cause active material to fall off. At the same time, it is difficult to achieve high capacity, excellent rate capability and long cycle stability. Summary of the Invention

[0005] In order to overcome the above-mentioned defects of the prior art, this application provides a self-supporting high-entropy phosphide anode material and its preparation method to solve the problems existing in the background art.

[0006] In a first aspect, this application provides a method for preparing a self-supporting high-entropy phosphide anode material, comprising: pretreating copper foam; preparing a mixed solution by co-dissolving five metal nitrates (cobalt nitrate, nickel nitrate, iron nitrate, copper nitrate, and bismuth nitrate) with urea in a solvent; immersing the pretreated copper foam in the mixed solution for a solvothermal reaction; washing and drying the hydrothermal product to obtain a copper foam-supported high-entropy hydroxide precursor; and phosphating the copper foam-supported high-entropy hydroxide precursor under an inert atmosphere to obtain a self-supporting high-entropy phosphide anode material.

[0007] In one possible implementation, the pretreatment of the copper foam includes: selecting copper foam with a length of 40 mm, a width of 20 mm, and a thickness of 1-3 mm, immersing it in dilute hydrochloric acid for 12-24 h; ultrasonically cleaning it with deionized water and ethanol, and vacuum drying it at 70-90 °C for 8-16 h.

[0008] In one possible implementation, the five metal nitrates are Co(NO3)2·6H2O, Ni(NO3)2·6H2O, Fe(NO3)3·9H2O, Cu(NO3)2·3H2O, and Bi(NO3)3·6H2O, with corresponding molar ratios of (0.20~0.4):(0.15~0.20):(0.15~0.20):(0.15~0.20):(0.15~0.20); and the molar ratio of urea to the total amount of the five metal nitrates is 5:1.

[0009] In one possible implementation, when the solvent is deionized water, the solvothermal reaction step includes: sequentially ultrasonically dissolving five metal nitrates and urea in deionized water to prepare a mixed solution; vertically immersing the pretreated copper foam into the mixed solution and placing it in a hydrothermal reactor, and carrying out a solvothermal reaction at 120~160℃ for 8~16h.

[0010] In one possible implementation, when the solvent is replaced with a mixture of isopropanol and glycerol, the volume ratio of isopropanol to glycerol is 48:12, the temperature of the solvothermal reaction is 180°C, and the reaction time is 12 hours.

[0011] In one possible implementation, the hydrothermal product is washed and dried to obtain a copper-foamed high-entropy hydroxide precursor, comprising: washing the hydrothermal product sequentially with deionized water and ethanol, and vacuum drying at 70~90℃ for 8~16h to obtain the copper-foamed high-entropy hydroxide precursor.

[0012] In one possible implementation, the phosphating treatment uses NaH2PO2·H2O as the phosphorus source; a quartz boat containing the phosphorus source is placed upstream of an argon inert atmosphere, and a quartz boat containing a copper foam-supported high-entropy hydroxide precursor is placed downstream of the argon inert atmosphere; the mass ratio of the phosphorus source to the copper foam-supported high-entropy hydroxide precursor is 10:1; the tail gas generated by the phosphating treatment is recovered using a copper sulfate solution.

[0013] In one possible implementation, the argon flow rate in the argon inert atmosphere is 50~100 sccm, the heating rate is 1~3℃ / min, the heat treatment temperature is 300~500℃, and the holding time is 2~4h.

[0014] In one possible implementation, the self-supporting high-entropy phosphide anode material is a single-phase solid solution with five metal elements—cobalt, nickel, iron, copper, and bismuth—uniformly distributed, and the mixed configuration entropy of this single-phase solid solution is... satisfy ;in, This is the universal gas constant.

[0015] Secondly, this application provides a self-supporting high-entropy phosphide anode material, which is prepared by the same method as the self-supporting high-entropy phosphide anode material and is used as the anode of a metal-ion battery.

[0016] The beneficial effects of this application are: the copper foam substrate and the high-entropy hydroxide precursor achieve a stable bond through chemical bonding. The specific bonding mechanism is as follows: after the copper foam is pretreated with dilute hydrochloric acid, the surface oxide layer is completely removed, and at the same time, a micro-rough structure and hydroxyl (-OH) active sites are formed on the substrate surface. During the solvothermal reaction, the metal-oxygen bonds in the in-situ grown high-entropy hydroxide can form MO-Cu (five metal-oxygen-copper) bridging chemical bonds with copper atoms on the surface of copper foam through oxygen atoms. This strong interfacial bonding can still be partially retained after subsequent high-temperature phosphating treatment, effectively ensuring the bonding strength between the high-entropy phosphide active material and the copper foam substrate, avoiding the shedding of active material during cycling, and significantly improving the long-term cycling stability of the electrode. At the same time, copper foam itself is a highly conductive three-dimensional metal framework. After phosphating, the substrate generates a conductive Cu3P phase, which has a high lattice matching degree with the five-element high-entropy phosphide and excellent interfacial conductivity synergy. Therefore, no additional binder or conductive agent needs to be introduced when assembling the battery, which avoids the energy density loss, ion and electron transport obstruction and active material shedding during cycling caused by binders, and simplifies the electrode preparation process.

[0017] By utilizing the high entropy effect and three-dimensional nanostructure, the volume expansion and structural pulverization problems of phosphides during charge and discharge processes are effectively mitigated, improving electronic conductivity and structural stability. Simultaneously, the copper foam substrate and phosphides exhibit a synergistic effect, significantly enhancing the rate performance and cycle life of the anode material. The fabrication process is simple and low-cost, making it suitable for large-scale energy storage systems. Attached Figure Description

[0018] The present application will be further described below with reference to the accompanying drawings and embodiments.

[0019] Figure 1 This is a flowchart illustrating a method for preparing a self-supporting high-entropy phosphide anode material, as provided in an embodiment of this application. Detailed Implementation

[0020] Various exemplary embodiments of this application are now described in detail. This detailed description should not be considered as a limitation of this application, but rather as a more detailed description of certain aspects, features, and implementations of this application.

[0021] It should be understood that the terminology used in this application is merely for describing particular embodiments and is not intended to limit the application. Furthermore, for numerical ranges in this application, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Each smaller range between any stated value or intermediate value within a stated range, and any other stated value or intermediate value within said range, is also included in this application. The upper and lower limits of these smaller ranges may be independently included or excluded from the range.

[0022] Unless otherwise stated, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art described herein. While only preferred methods and materials are described herein, any methods and materials similar or equivalent to those described herein may be used in the implementation or testing of this application. All references to this specification are incorporated by way of citation to disclose and describe methods and / or materials associated with those references. In the event of any conflict with any incorporated reference, the content of this specification shall prevail.

[0023] Various modifications and variations can be made to the specific embodiments described in this application without departing from the scope or spirit of this application, as will be apparent to those skilled in the art. Other embodiments derived from this application will also be obvious to those skilled in the art. This application specification and embodiments are merely exemplary.

[0024] The terms “include,” “including,” “have,” “contain,” etc., used in this article are all open-ended terms, meaning that they include but are not limited to.

[0025] This application provides a method for preparing a self-supporting high-entropy phosphide anode material, such as... Figure 1 As shown, the method includes steps S101 to S103. Wherein, Figure 1 This is merely one execution order shown in the embodiments of this application and does not represent the only execution order for a method of preparing a self-supporting high-entropy phosphide anode material. Where the final result can be achieved... Figure 1 The steps shown can be performed in parallel or in reverse order.

[0026] Step S101: Pre-treat the copper foam.

[0027] The pretreatment of copper foam includes the following steps.

[0028] Select copper foam with a length of 40mm, a width of 20mm, and a thickness of 1~3mm, and soak it in 20% dilute hydrochloric acid for 12~24h.

[0029] The sample was ultrasonically cleaned with deionized water and ethanol, and then vacuum dried at 70-90℃ for 8-16 hours.

[0030] The dimensions and thickness of the copper foam were specifically defined, and the design basis for each parameter is as follows.

[0031] The length of the copper foam is selected to be 40mm, which matches the inner diameter of the hydrothermal reactor of about 40mm. The copper foam can be placed vertically in the hydrothermal reactor to ensure a uniform solution flow environment, so that the high-entropy hydroxide precursor can grow uniformly on the surface of the copper foam substrate.

[0032] A thickness of 1-3 mm for copper foam is the optimal range after balancing electrochemical performance and active material loading. If thicker copper foam (4 mm or more) is used, the internal pore structure is more developed, allowing for the loading of more active material; however, the diffusion path of metal ions within the pores increases, resulting in poorer electrolyte wetting and weaker rapid charge / discharge capability. If thinner copper foam (around 1 mm) is used, the ion transport distance is shorter, electrolyte wetting is more thorough, and charge / discharge performance is better.

[0033] Therefore, thinner copper foam (1-3 mm) provides the material with good conductivity and synergistic effect, allowing for faster sodium ion transport and better charge / discharge performance.

[0034] It should be noted that the electrochemically active material of the negative electrode in this application is a five-element high-entropy phosphide consisting of cobalt, nickel, iron, copper, and bismuth. The high-entropy hydroxide precursor prepared by solvothermal reaction is only a precursor for the phosphating reaction. After high-temperature phosphating treatment, it is converted into a high-entropy phosphide active material with efficient sodium storage performance. The high-entropy phosphide with efficient sodium storage performance is the core electrochemically active component of the electrode, which is in-situ immobilized on a three-dimensional foamed copper framework, together constituting the self-supporting high-entropy phosphide negative electrode material of this application.

[0035] Step S102: Five metal nitrates, namely cobalt nitrate, nickel nitrate, iron nitrate, copper nitrate and bismuth nitrate, are dissolved with urea in a solvent to prepare a mixed solution. The pretreated copper foam is then immersed in the mixed solution for a solvothermal reaction. The hydrothermal product is washed and dried to obtain a copper foam-supported high-entropy hydroxide precursor.

[0036] Specifically, this application selects five metallic elements—iron, cobalt, nickel, copper, and bismuth—to construct a pentagonal high-entropy system. The element selection and synergistic mechanism are as follows: Fe, Co, Ni, and Cu can combine with phosphorus to form metal phosphides, all of which achieve sodium storage through conversion reactions. Among them, Fe, Co, and Ni can provide higher capacity for the electrode material. The combination of phosphorus and Cu to form metal phosphides can improve the reversibility, conductivity, and stability of phosphorus-based anode materials to a certain extent. Moreover, the five metallic elements have similar atomic radii, making them easier to fuse and laying the structural foundation for the formation of a uniform single-phase solid solution. The phosphides formed by Bi and phosphorus can follow a two-step sodium storage mechanism of "conversion-alloying".

[0037] During discharge, metal phosphides (M x P y Sodium ions undergo a conversion reaction with sodium ions to produce sodium phosphide (such as Na3P) and a metallic element (M). Subsequently, sodium ions further undergo an alloying reaction with the metallic element (Bi) produced in the conversion reaction to form a sodium-metal alloy. The alloying reaction can contribute additional sodium storage capacity, thereby increasing the material capacity. The stepwise reaction can effectively alleviate instantaneous stress accumulation and improve cycle stability.

[0038] Furthermore, the matching combination of the five metals comprehensively considers electronegativity compatibility, redox reaction compatibility, and the rationality of the long distribution of MP bonds (the five metal-phosphorus chemical bonds) to ensure the formation of a stable high-entropy single-phase structure. Replacing any one of the metal elements would directly disrupt the elemental matching equilibrium of the system, making it impossible to form a structurally stable single-phase solid solution, resulting in a decrease in the material's electrochemical sodium storage performance and structural cycle stability.

[0039] The five metal nitrates are Co(NO3)2·6H2O, Ni(NO3)2·6H2O, Fe(NO3)3·9H2O, Cu(NO3)2·3H2O, and Bi(NO3)3·6H2O, with corresponding molar ratios of (0.20~0.4):(0.15~0.20):(0.15~0.20):(0.15~0.20):(0.15~0.20).

[0040] The molar ratio of urea to the total amount of five metal nitrates is 5:1.

[0041] Specifically, this application employs a solvothermal method to prepare a high-entropy hydroxide precursor supported on copper foam. The core objective is to achieve in-situ nucleation and uniform growth of high-entropy hydroxide on the surface of the copper foam framework, forming a robust three-dimensional nanoarray structure. This in-situ growth process eliminates the need for additional binders and conductive agents in the final electrode, avoiding energy density loss, ion and electron transport obstruction, and active material shedding during cycling caused by binders, while also simplifying the electrode fabrication process. The pretreated copper foam possesses a three-dimensional porous network structure, providing ample buffer space for the volume expansion of the self-supporting high-entropy phosphide anode material obtained after subsequent phosphating during sodium ion insertion / extraction. The uniform array structure formed by in-situ growth exposes more active sites, increasing the contact area between the active material and the electrolyte, and improving the sodium ion transfer rate.

[0042] When the solvent is deionized water, the solvothermal reaction steps include the following:

[0043] Five metal nitrates and urea were sequentially ultrasonically dissolved in deionized water to prepare a mixed solution.

[0044] The pretreated copper foam was vertically immersed into the mixed solution and placed in a hydrothermal reactor, where it underwent a solvothermal reaction at 120-160°C for 8-16 hours.

[0045] When the solvent is replaced with a mixture of isopropanol and glycerol, the volume ratio of isopropanol to glycerol is 48:12, the temperature of the solvothermal reaction is 180℃, and the reaction time is 12h.

[0046] Specifically, compared to deionized water solvents, the organic mixed solvent composed of isopropanol and glycerol has superior ion dispersion ability and suitable solvent viscosity.

[0047] A stable bond is achieved between the copper foam substrate and the high-entropy hydroxide precursor through chemical bonding. The specific bonding mechanism is as follows: After pretreatment with dilute hydrochloric acid, the oxide layer on the surface of the copper foam is completely removed, and a micro-rough structure and hydroxyl (-OH) active sites are formed on the substrate surface. During the solvothermal reaction, the metal-oxygen bonds in the in-situ grown high-entropy hydroxide can form MO-Cu (five metal-oxygen-copper) bridging chemical bonds with copper atoms on the surface of the copper foam through oxygen atoms. This strong interfacial bonding effect can still be partially retained after subsequent high-temperature phosphating treatment, effectively ensuring the bonding strength between the high-entropy phosphide active material and the copper foam substrate, avoiding the shedding of active material during cycling, and significantly improving the long-term cycling stability of the electrode. At the same time, the copper foam itself is a highly conductive three-dimensional metal framework. After phosphating, the substrate generates a conductive Cu3P phase, which has a high lattice matching degree with the five-element high-entropy phosphide and excellent interfacial conductivity synergy. Therefore, no additional binder or conductive agent is needed when assembling the battery.

[0048] The hydrothermal products are washed and dried to obtain a copper-foamed high-entropy hydroxide precursor, which includes the following:

[0049] The hydrothermal products were washed sequentially with deionized water and ethanol, and then vacuum dried at 70-90℃ for 8-16 h to obtain a copper foam-supported high-entropy hydroxide precursor.

[0050] Step S103: Phosphate the high-entropy hydroxide precursor supported on copper foam under an inert atmosphere to obtain a self-supporting high-entropy phosphide anode material.

[0051] Specifically, the purpose of the phosphating process is to use phosphine (PH3) gas to convert high-entropy hydroxides into high-entropy phosphides with higher capacity and better conductivity, thereby improving the sodium storage performance and recycling performance of the negative electrode material.

[0052] Compared to anode materials such as hard carbon transition metal oxides, transition metal phosphides possess higher specific capacity and a lower discharge plateau. Hydroxides, on the other hand, lack effective sodium storage activity and exhibit extremely poor electronic conductivity. Phosphating is a crucial step in transforming electrochemically inactive precursors into active phases, simultaneously introducing phosphorus into the crystal lattice to construct MP (five metal-phosphorus chemical bonds) structural units with sodium storage capabilities.

[0053] The phosphating treatment used NaH₂PO₂·H₂O (sodium hypophosphite) as the phosphorus source. A quartz boat containing the phosphorus source was placed upstream of an argon-inert atmosphere, while a quartz boat containing a copper-foam-supported high-entropy hydroxide precursor was placed downstream of the argon-inert atmosphere. This method ensures unidirectional gas flow through the sample.

[0054] Specifically, under high-temperature heat treatment in an inert atmosphere, sodium hypophosphite decomposes upon heating to produce phosphine (PH3) gas. The generated phosphine gas undergoes a gas-solid phosphating reaction with the high-entropy hydroxide precursor supported on copper foam, achieving a phase transformation and producing a five-element high-entropy phosphide with excellent electrochemical performance.

[0055] The argon flow rate in the argon inert atmosphere was 50-100 sccm, the heating rate was 1-3℃ / min, the heat treatment temperature was 300-500℃, and the holding time was 2-4h. The mass ratio of phosphorus source to copper foam-supported high-entropy hydroxide precursor was 10:1.

[0056] The exhaust gas generated during phosphating is recovered using a 2% copper sulfate solution.

[0057] Specifically, trace amounts of toxic exhaust gas are generated during the phosphating process. Copper sulfate solution is used to absorb and recover the phosphating exhaust gas during the experiment to avoid pollution risks and ensure experimental safety and environmental protection.

[0058] The self-supporting high-entropy phosphide anode material is a single-phase solid solution with five metal elements uniformly distributed: cobalt, nickel, iron, copper, and bismuth. The mixed configuration entropy of this single-phase solid solution... satisfy .in, This is the universal gas constant.

[0059] Specifically, for a single-phase solid solution with multiple components uniformly distributed, the quantitative relationship between the system's mixing configuration entropy and phase stability satisfies the entropy calculation formula: ;in, Mixed configuration entropy refers to the entropy value corresponding to the degree of disorder in the atomic arrangement when multiple metal atoms are randomly mixed in the same crystal lattice. That is, a high-entropy single-phase solid solution. This is the universal gas constant. The total number of metallic components is 5-element system in this application. (Cobalt, nickel, iron, copper, bismuth) For the component counting subscript, For the first mole fraction of a metallic element , This is the operator for the natural logarithm.

[0060] According to the formula, the system configuration entropy reaches its theoretical maximum of 1.61R when the molar fractions of the five metal elements are completely equal. This application specifies the five metal nitrates as Co(NO3)2·6H2O, Ni(NO3)2·6H2O, Fe(NO3)3·9H2O, Cu(NO3)2·3H2O, and Bi(NO3)3·6H2O, with corresponding molar ratios of (0.20~0.4):(0.15~0.20):(0.15~0.20):(0.15~0.20):(0.15~0.20). Within this range, when cobalt (Co) is at the lower limit of 0.20 and the other four metals are at the upper limit of 0.20, the proportions of the five metals are completely equal, and the mixed configuration entropy can reach 1.61R. The system's mixed configuration entropy is exactly 1.5R under the extreme boundary ratio of the range (cobalt is 0.4, and the other four metals are all 0.15), which just meets the criteria for high-entropy materials. By adjusting the molar ratio of the five metal precursors within this range, the system configuration entropy can be continuously changed, thereby exploring the influence of different entropy values ​​on the electrochemical and crystal structure performance of the anode material.

[0061] The core principle of this application's five-element high-entropy design approach is as follows. High entropy refers to the introduction of five or more elements at the same lattice location to form a single-phase solid solution structure, which exhibits superior performance due to its entropy stabilization effect and the synergistic effect between multiple elements. By selecting beneficial element combinations and adjusting their atomic concentrations, high-entropy materials that meet specific requirements can be customized.

[0062] The high-entropy effect can simultaneously improve the coulombic efficiency and crystal structure stability of the electrode. The three-dimensional nanostructure formed after phosphating can expose more active sites, thereby improving the reversible capacity. This opens up a new direction for the development of high-performance sodium-ion battery anodes.

[0063] This application provides a self-supporting high-entropy phosphide anode material, which is prepared by a method for preparing self-supporting high-entropy phosphide anode materials and is used as the anode of a metal-ion battery. The metal-ion battery is preferably a sodium-ion battery.

[0064] It is understood that all raw materials used in the embodiments of this application can be purchased commercially.

[0065] In order to gain a more detailed understanding of the features and technical content of this application, the implementation of this application will be described in detail below with reference to the embodiments. The embodiments are for reference and illustration only and are not intended to limit this application.

[0066] Example 1

[0067] 1. Copper foam pretreatment: The copper foam was immersed in dilute hydrochloric acid for 12 hours, ultrasonically cleaned with deionized water and ethanol respectively, and vacuum dried at 80℃ for 12 hours. The size of the copper foam in the experiment was 40×20×1mm.

[0068] 2. Precursor preparation: 0.8 mmol Co(NO3)2·6H2O, 0.8 mmol Ni(NO3)2·6H2O, 0.8 mmol Fe(NO3)3·9H2O, 0.8 mmol Cu(NO3)2·3H2O, 0.8 mmol Bi(NO3)3·6H2O, and 20 mmol CO(NH2)2 urea were added to a mixture of 48 ml isopropanol and 12 ml glycerol and dissolved by ultrasonication. The mixture was then subjected to hydrothermal reaction at 180 °C for 12 h in a 100 ml hydrothermal reactor. The resulting hydrothermal product was washed sequentially with deionized water and ethanol, and then vacuum dried at 80 °C for 12 h to obtain a copper foam-supported high-entropy hydroxide precursor.

[0069] 3. Preparation of High-Entropy Phosphate: A high-entropy hydroxide precursor supported on copper foam and 0.6 g of NaH2PO2·H2O were placed in downstream and upstream quartz boats, respectively. The argon gas flow rate during phosphating was 80 sccm, the heating rate was 2℃ / min, the heat treatment temperature was 400℃, and the holding time was 3 h. Sodium hypophosphite (NaH2PO2·H2O) decomposed to produce PH3 gas, which reacted with the high-entropy hydroxide precursor in a gas-solid phosphating reaction, ultimately yielding a self-supporting high-entropy phosphate anode material.

[0070] Self-supporting high-entropy phosphide anode material was cut into 12mm discs to serve as sodium-ion battery electrodes, and sodium metal sheets were used as counter electrodes to assemble button cells.

[0071] It should be noted that the 12mm electrode in this embodiment is only a preferred specification for this test. In actual applications, the electrode size can be adjusted according to the battery casing model and device requirements. The scope of protection of this application is not limited by this cutting size.

[0072] Example 2

[0073] The difference between this embodiment and Example 1 is that the amounts of the five metal nitrates used are adjusted to 1.6 mmol Co(NO3)2·6H2O, 0.6 mmol Ni(NO3)2·6H2O, 0.6 mmol Fe(NO3)3·9H2O, 0.6 mmol Cu(NO3)2·3H2O, and 0.6 mmol Bi(NO3)3·6H2O. The rest is the same as in Example 1.

[0074] Comparative Example 1

[0075] The difference between Comparative Example 1 and Example 1 is that the copper foam was replaced with nickel foam during the hydrothermal process; otherwise, they are the same as in Example 1.

[0076] Table 1. Statistical Table of Electrochemical Performance Test Results

[0077]

[0078] Example 1 uses a phosphating process, utilizing phosphine gas to convert high-entropy hydroxide into high-entropy phosphide with higher capacity and better conductivity. A self-supporting high-entropy phosphide anode material was successfully prepared. The electrochemical test data in Table 1 show that, at different current densities, the specific capacity measured in Example 1 is significantly higher than that in Example 2, exhibiting superior rate performance. This performance difference is mainly attributed to the higher configurational entropy of the system in Example 1. According to the entropy calculation formula, when the molar fractions of the five metal elements are completely equal, the entropy value is 1.61R. In Example 2, when the molar ratio of the five metal nitrates is 0.4:0.15:0.15:0.15, the material entropy value is 1.5R. This indicates that the enhanced entropy effect is beneficial to improving electrode reaction kinetics and structural reversibility.

[0079] Compared to Comparative Example 1, Example 1 with a copper foam substrate exhibits superior rate performance. Copper has higher conductivity than nickel, and Cu3P is formed on the surface of the copper foam after phosphating. The nickel foam, under phosphating conditions, produces Ni2P / Ni... 12 Although P5 is also active, its lattice matching and interfacial bonding with high-entropy phosphides are not as good as those of the Cu3P system, which confirms that copper phosphide foam has a better synergistic conductivity with high-entropy active materials.

[0080] While this application provides the method operation steps as described in the embodiments or flowcharts, more or fewer operation steps may be included based on conventional or non-inventive labor. The order of steps listed in this embodiment is merely one possible execution order among many and does not represent the only possible execution order.

[0081] The above embodiments are only used to illustrate the technical solutions of this application, and are not intended to limit this application. Although this application has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of this application.

Claims

1. A method for preparing a self-supporting high-entropy phosphide anode material, characterized in that, include: Pretreatment of copper foam; Five metal nitrates, namely cobalt nitrate, nickel nitrate, iron nitrate, copper nitrate, and bismuth nitrate, were dissolved with urea in a solvent to prepare a mixed solution. Pretreated copper foam was then immersed in the mixed solution for a solvothermal reaction. The hydrothermal product was washed and dried to obtain a copper foam-supported high-entropy hydroxide precursor. A self-supporting high-entropy phosphide anode material was prepared by phosphating a copper foam-supported high-entropy hydroxide precursor under an inert atmosphere.

2. The method for preparing the self-supporting high-entropy phosphide anode material according to claim 1, characterized in that, The pretreatment of the foamed copper includes: Select copper foam with a length of 40mm, a width of 20mm, and a thickness of 1~3mm, and soak it in dilute hydrochloric acid for 12~24h; The sample was ultrasonically cleaned with deionized water and ethanol, and then vacuum dried at 70-90℃ for 8-16 hours.

3. The method for preparing the self-supporting high-entropy phosphide anode material according to claim 1, characterized in that, The five metal nitrates are Co(NO3)2·6H2O, Ni(NO3)2·6H2O, Fe(NO3)3·9H2O, Cu(NO3)2·3H2O, and Bi(NO3)3·6H2O, with corresponding molar ratios of (0.20~0.4):(0.15~0.20):(0.15~0.20):(0.15~0.20):(0.15~0.20). The molar ratio of urea to the total amount of five metal nitrates is 5:

1.

4. The method for preparing the self-supporting high-entropy phosphide anode material according to claim 1, characterized in that, When the solvent is deionized water, the solvothermal reaction steps include: Five metal nitrates and urea were sequentially ultrasonically dissolved in deionized water to prepare a mixed solution; The pretreated copper foam was vertically immersed into the mixed solution and placed in a hydrothermal reactor, where it underwent a solvothermal reaction at 120-160°C for 8-16 hours.

5. The method for preparing the self-supporting high-entropy phosphide anode material according to claim 4, characterized in that, When the solvent is replaced with a mixture of isopropanol and glycerol, the volume ratio of isopropanol to glycerol is 48:12, the temperature of the solvothermal reaction is 180°C, and the reaction time is 12 hours.

6. The method for preparing the self-supporting high-entropy phosphide anode material according to claim 1, characterized in that, The hydrothermal products are washed and dried to obtain a copper-foamed, high-entropy hydroxide precursor, comprising: The hydrothermal products were washed sequentially with deionized water and ethanol, and then vacuum dried at 70-90℃ for 8-16 h to obtain a copper foam-supported high-entropy hydroxide precursor.

7. The method for preparing the self-supporting high-entropy phosphide anode material according to claim 1, characterized in that, The phosphating treatment uses NaH2PO2·H2O as the phosphorus source; A quartz boat containing a phosphorus source is placed upstream of an argon inert atmosphere, and a quartz boat containing a high-entropy hydroxide precursor supported on copper foam is placed downstream of an argon inert atmosphere. The mass ratio of phosphorus source to copper foam-supported high-entropy hydroxide precursor was 10:1; The tail gas generated during phosphating is recovered using copper sulfate solution.

8. The method for preparing the self-supporting high-entropy phosphide anode material according to claim 7, characterized in that, The flow rate of argon gas in the argon inert atmosphere is 50~100 sccm, the heating rate is 1~3℃ / min, the heat treatment temperature is 300~500℃, and the holding time is 2~4h.

9. The method for preparing the self-supporting high-entropy phosphide anode material according to claim 1, characterized in that, The self-supporting high-entropy phosphide anode material is a single-phase solid solution with five metal elements—cobalt, nickel, iron, copper, and bismuth—uniformly distributed. The mixed configuration entropy of this single-phase solid solution... satisfy ;in, This is the universal gas constant.

10. A self-supporting high-entropy phosphide anode material, characterized in that, The self-supporting high-entropy phosphide anode material is prepared by the preparation method of the self-supporting high-entropy phosphide anode material according to any one of claims 1 to 9, and is applied to the anode of a metal-ion battery.